Effects of Dietary n-3 Polyunsaturated Fatty Acids and Selenomethionine on Meat Quality and Fatty Acid Composition in Finishing Pigs - Yunju Yin; Hu Zhang; Teng Hui; Ran Li; Hong Chen; Minquan Xia; Bin Feng; Yong Yang; Yaowen Liu; Zhengfeng Fang (Foods)
The interaction between selenomethionine (SeMet) and n-3 polyunsaturated fatty acids (n-3 PUFA) in producing n-3 PUFA-enriched pork remains unknown. This study investigates the effect of different n-3 PUFA sources (linseed oil vs. fish oil) and SeMet supplementation on meat quality and fatty acid composition in finishing pigs. Key findings demonstrate that dietary supplementation with 0.3 mg/kg SeMet significantly enhances the L*24h value (lightness) of the longissimus thoracis et lumborum (LTL) tissue compared to 3% linseed oil or fish oil treatments alone (p < 0.05). Pork flavor improvement is further supported by increased serine content (p < 0.05) and a notable tendency toward elevated total sweet amino acids (Thr + Ser + Gly + Ala + Pro) in LTL tissue (p = 0.077). Compared with 3% sunflower oil (control group), 3% linseed oil or fish oil significantly enhances n-3 PUFA content while reducing the n-6/n-3 ratio in both LTL and subcutaneous adipose tissue (p < 0.05). The synergistic interaction between SeMet and oil (linseed oil or fish oil) is observed, increasing α-linolenic acid (ALA; C18:3n-3), eicosatrienoic acid (C20:3n-3), and total n-3 PUFA deposition in subcutaneous fat tissue (p < 0.05). SeMet increases the activities of total superoxide dismutase (T-SOD) and catalase (CAT). Meanwhile, the SeMet-fish oil combination decreases lipids oxidation compared to individual treatments (p < 0.05). Collectively, 3% linseed oil or fish oil effectively enhances unsaturated fatty acid profiles, while concurrent SeMet addition may synergistically enhance certain nutritional attributes (improved oxidative stability) and sensory scores (enhanced L24 h* value and flavor precursors). We, therefore, recommend adding 0.3 mg/kg SeMet to the n-3 PUFA-enriched pork production process.